A method for gasoline hydrodesulfurization
By using a core-shell structure catalyst and a two-stage process, the problems of easy carbon buildup, poisoning, and corrosion of catalysts in gasoline hydrodesulfurization have been solved, achieving ultra-deep desulfurization and low octane number loss, extending catalyst life, and adapting to upgraded environmental regulations.
Patent Information
- Application Number
- CN202611250673.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-08-18
AI Technical Summary
Existing gasoline hydrodesulfurization technology cannot simultaneously achieve ultra-deep desulfurization, low octane number loss, and long-term stable operation. The catalyst is prone to carbon buildup, poisoning, and corrosion, leading to activity decay, and uneven reaction results in low desulfurization rate.
The catalyst employs a core-shell structure. The first catalyst core is citric acid-modified alumina supported on nickel phosphide, with an outer layer of polydopamine. The second catalyst core is ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve supported on cobalt molybdenum sulfide, with an outer layer of sulfonated carbon coating. Through a two-stage selective hydrogenation-desulfurization process combined with gas-liquid separation steps, the catalyst activity and selectivity are ensured.
It achieves ultra-deep desulfurization of fluidized catalytic cracking gasoline, with sulfur content ≤10μg/g, octane number loss ≤1.5 units, extended catalyst life, improved reaction stability, and meets the requirements of upgraded environmental regulations.
Abstract
Description
Technical Field
[0001] This application relates to the field of petrochemical oil refining technology, and in particular to a method for hydrogenating and desulfurizing gasoline. Background Technology
[0002] Gasoline hydrodesulfurization is a core technology in petrochemical oil refining. With the continuous tightening of global environmental regulations on fuel sulfur content limits and the automotive industry's stringent requirements for clean fuel octane retention, the demand for its industrial application is constantly expanding. According to industry statistics, fluidized bed catalytic cracking gasoline, a major component of gasoline consumption in my country, accounts for over 85% of the technological demand for deep desulfurization and octane protection. This type of gasoline, due to its high olefin content and complex sulfide composition, places extremely high demands on the selectivity of the desulfurization process and the stability of the catalyst. However, existing gasoline hydrodesulfurization technologies are limited by catalyst performance and reaction process compatibility, making it difficult to simultaneously meet the requirements of ultra-deep desulfurization, low octane loss, and long-cycle operation. This results in high production costs for clean gasoline and frequent catalyst replacements, severely hindering the green upgrading of the oil refining industry.
[0003] To address the challenge of deep desulfurization in fluidized catalytic cracking of gasoline, the industry has successively developed various technical routes, including traditional cobalt-molybdenum catalyst hydrogenation, nickel-based catalyst selective hydrogenation, molecular sieve-modified catalysis, and segmented temperature-controlled hydrogenation. While traditional cobalt-molybdenum catalyst hydrogenation technology offers high desulfurization efficiency, it easily leads to olefin oversaturation, resulting in an octane number loss of 3-5 units. Nickel-based catalyst selective hydrogenation technology can reduce octane number loss, but the catalyst has weak resistance to carbon buildup and nitrogen poisoning, with an operating cycle of only 1000-1500 hours. Molecular sieve-modified catalysis technology improves selectivity by regulating acidic sites, but the molecular sieve support is easily corroded by hydrogen sulfide and organic acids, resulting in poor structural stability. While segmented temperature-controlled hydrogenation technology can optimize the reaction process, it suffers from uneven gas-liquid-solid three-phase contact, leading to incomplete local reactions and making it difficult to achieve a desulfurization rate exceeding 98%. Furthermore, existing technologies often employ catalysts with a single active component supported structure, lacking effective surface protection mechanisms. These catalysts are susceptible to contamination from gums and alkaline nitrides in the feedstock, leading to rapid activity decay and further increasing industrial application costs.
[0004] In view of the above-mentioned technical defects, there is an urgent need to improve the existing gasoline hydrodesulfurization technology. Summary of the Invention
[0005] In view of this, this application provides a method for hydrodesulfurization of gasoline, which achieves ultra-deep desulfurization, low octane number loss and long-term stable operation of fluidized catalytic cracking gasoline, and avoids the problem of activity decay caused by catalyst carbon deposit, poisoning and corrosion. The prepared low-sulfur clean gasoline has a sulfur content ≤10μg / g and an octane number loss ≤1.5 units, which is suitable for the clean fuel production requirements under the upgrading of environmental regulations.
[0006] This application discloses a method for hydrodesulfurization of gasoline, comprising the following steps: pre-treating fluidized catalytic cracking gasoline and mixing it with hydrogen, performing a selective hydrogenation reaction, and taking the liquid phase product; subjecting the liquid phase product to a desulfurization reaction to obtain low-sulfur clean gasoline; the selective hydrogenation reaction is carried out under the catalysis of a first catalyst, the first catalyst having a core-shell structure, the core of the first catalyst being citric acid-modified alumina supported nickel phosphide, and the outer layer of the first catalyst being polydopamine; the desulfurization reaction is carried out under the catalysis of a second catalyst, the second catalyst having a core-shell structure, the core of the second catalyst being ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve supported cobalt molybdenum sulfide, and the outer layer of the second catalyst being a sulfonated carbon coating layer.
[0007] Optionally, the preparation method of the first catalyst includes the following steps: mixing alumina, citric acid and water, and then modifying the mixture to obtain citric acid-modified alumina; mixing the citric acid-modified alumina, nickel nitrate and ammonium dihydrogen phosphate, and then reducing the mixture to obtain alumina-supported nickel phosphide; mixing the alumina-supported nickel phosphide, dopamine and water, and then coating the mixture, followed by drying and calcination to obtain the first catalyst.
[0008] Optionally, the mass-volume ratio of the alumina, citric acid, and water is 1 g : (0.03~0.06) g : (1~3) mL. Optionally, the mass ratio of the citric acid-modified alumina, nickel nitrate, and ammonium dihydrogen phosphate is 1 : (0.08~0.15) : (0.04~0.08).
[0009] Optionally, the mass-to-volume ratio of the alumina-supported nickel phosphide, dopamine, and water is 1 g: (0.02~0.05) g: (1~2) mL.
[0010] Optionally, the modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 40~60℃, and a time of 2~3 h.
[0011] Optionally, the reduction process is carried out in a hydrogen atmosphere at a temperature of 350-400°C for 3-4 hours.
[0012] Optionally, the coating treatment is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 25~35℃, and a time of 2~3 h.
[0013] Optionally, the drying temperature is 90~110℃ and the time is 3~4h.
[0014] Optionally, the calcination is carried out under an inert atmosphere at a temperature of 200-250°C for 2-3 hours.
[0015] Optionally, the preparation method of the second catalyst includes the following steps: mixing ZSM-5 molecular sieve, ethylenediaminetetraacetic acid (EDTA), and water, then modifying the mixture and drying it to obtain EDTA-modified ZSM-5 molecular sieve; mixing the EDTA-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate, then impregnating, calcining, and sulfiding the mixture to obtain ZSM-5 molecular sieve-supported cobalt-molybdenum sulfide; and mixing the ZSM-5 molecular sieve-supported cobalt-molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid, then coating and carbonizing the mixture to obtain the second catalyst.
[0016] Optionally, the mass-to-volume ratio of the ZSM-5 molecular sieve, ethylenediaminetetraacetic acid, and water is 1 g: (0.03~0.06) g: (1~3) mL.
[0017] Optionally, the mass ratio of the ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate is 1:(0.04~0.08):(0.10~0.20).
[0018] Optionally, the mass ratio of the ZSM-5 molecular sieve loaded with cobalt molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid is 1:(0.05~0.10):(0.02~0.05).
[0019] Optionally, the modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 50~70℃, and a time of 1.5~2.5 h.
[0020] Optionally, the drying temperature is 90~110℃ and the time is 3~4h.
[0021] Optionally, the vulcanization treatment temperature is 280~320℃ and the time is 4~6h.
[0022] Optionally, the coating treatment is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 60~80℃, and a time of 1~2 h.
[0023] Optionally, the carbonization process is carried out under an inert atmosphere at a temperature of 400-450°C for 3-4 hours.
[0024] Optionally, the selective hydrogenation reaction is carried out under stirring conditions, with a stirring speed of 300-800 r / min, a temperature of 240-300℃, a pressure of 1.6-2.5 MPa, a hydrogen-to-oil volume ratio of 200-400, and a liquid hourly space velocity of 2.0-4.0 h⁻¹. -1 .
[0025] Optionally, the desulfurization reaction is carried out at a temperature of 300-330℃, a reaction pressure of 1.6-2.5 MPa, a hydrogen-to-oil volume ratio of 200-400, and a liquid hourly space velocity of 2.0-4.0 h⁻¹. -1 .
[0026] Optionally, the pretreatment of fluidized catalytic cracking gasoline specifically includes the following steps: mixing fluidized catalytic cracking gasoline, porous filter ceramic balls and dehydrating agent, purifying them, and then separating them to obtain pretreated fluidized catalytic cracking gasoline.
[0027] Optionally, the mass-to-volume ratio of the fluidized catalytic cracking gasoline, porous filter ceramic balls, and dehydrating agent is 1 g : (0.01~0.03) g : (0.02~0.05) mL.
[0028] Optionally, the purification process is carried out under stirring conditions, with a stirring speed of 300~500 r / min, a temperature of 25~35℃, and a time of 30~60 min.
[0029] Optionally, the low-sulfur clean gasoline has a sulfur content ≤10μg / g and an octane number loss ≤1.5 units.
[0030] The gasoline hydrodesulfurization method provided in this application achieves the synergistic effect of efficient loading of catalyst active components and surface protection mechanisms, adapting to the stepwise removal requirements of complex sulfides in fluidized catalytic cracking gasoline. It effectively solves the problems of low desulfurization rate, large octane number loss, and poor catalyst stability associated with traditional methods, and avoids problems such as activity decay due to catalyst carbon buildup, poisoning, and corrosion, as well as incomplete local desulfurization caused by uneven reaction. Therefore, compared with existing technologies, the gasoline hydrodesulfurization method provided in this application has the advantages of high desulfurization efficiency, good octane number retention, long catalyst life, excellent process stability, and both practicality and industrial adaptability. Detailed Implementation
[0031] The technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific implementation methods described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0032] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.
[0033] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0034] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0035] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0036] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0037] This application discloses a method for hydrodesulfurization of gasoline, comprising the following steps: pre-treating fluidized catalytic cracking gasoline and mixing it with hydrogen, performing a selective hydrogenation reaction, and taking the liquid phase product; subjecting the liquid phase product to a desulfurization reaction to obtain low-sulfur clean gasoline; the selective hydrogenation reaction is carried out under the catalysis of a first catalyst, the first catalyst having a core-shell structure, the core of the first catalyst being citric acid-modified alumina supported nickel phosphide, and the outer layer of the first catalyst being polydopamine; the desulfurization reaction is carried out under the catalysis of a second catalyst, the second catalyst having a core-shell structure, the core of the second catalyst being ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve supported cobalt molybdenum sulfide, and the outer layer of the second catalyst being a sulfonated carbon coating layer.
[0038] It should be noted that the gasoline hydrodesulfurization method of this application achieves an orderly connection between sulfide conversion and deep removal through a two-stage core process of selective hydrodesulfurization-desulfurization. This solves the problems of uneven reaction, incomplete desulfurization, and easy catalyst contamination in traditional processes. Moreover, the process parameters are controllable throughout the entire process, and each reaction unit can be continuously operated through pipeline transportation. During transportation, the material properties can be monitored in real time by an online sulfur content detector to ensure stable product quality. There are no harsh operating conditions, making it easy to promote industrialization.
[0039] In some embodiments, after the selective hydrogenation reaction is completed, the resulting selective hydrogenation product is a gas-liquid mixture comprising liquid gasoline product, unreacted hydrogen, and hydrogen sulfide gas generated in the reaction. To protect the catalyst activity of subsequent desulfurization reactions and improve desulfurization efficiency, the reaction effluent needs to be separated into gas and liquid phases.
[0040] Specifically, the selective hydrogenation reaction effluent is subjected to gas-liquid separation to remove unreacted hydrogen and generated gaseous components such as hydrogen sulfide. The collected liquid phase is the liquid product after selective hydrogenation. This liquid product is mainly hydrotreated gasoline that has undergone selective hydrogenation pretreatment, in which olefins are partially saturated and the sulfide form has been transformed, making it suitable as feedstock for subsequent deep desulfurization reactions.
[0041] It should be noted that the gas-liquid separation can be achieved using conventional gas-liquid separation methods in the art. This application does not specifically limit the method of gas-liquid separation, as long as it can effectively remove gaseous components and obtain liquid products that meet the feed requirements of the desulfurization reaction. If the reaction products containing hydrogen sulfide are directly introduced into the desulfurization reactor without the above-mentioned gas-liquid separation, hydrogen sulfide will compete with the cobalt-molybdenum sulfide active phase in the second catalyst for adsorption, inhibiting the adsorption and activation of thiophene sulfides by the active sites. At the same time, high concentrations of hydrogen sulfide will also exacerbate the sulfur poisoning process of the catalyst and equipment corrosion. This application effectively eliminates the poisoning interference of hydrogen sulfide on the second catalyst by setting a gas-liquid separation step between the selective hydrogenation reaction and the desulfurization reaction. This ensures that the selective adsorption function of the sulfonated carbon coating layer in the core-shell structure of the second catalyst and the deep hydrogenation desulfurization capacity of the cobalt-molybdenum sulfide active phase are fully utilized, which is a key process connection for achieving ultra-deep desulfurization and long-term stable operation.
[0042] In some embodiments, the preparation method of the first catalyst includes the following steps: mixing alumina, citric acid and water, and then performing a modification treatment to obtain citric acid-modified alumina; mixing the citric acid-modified alumina, nickel nitrate and ammonium dihydrogen phosphate, and then performing a reduction treatment to obtain alumina-supported nickel phosphide; mixing the alumina-supported nickel phosphide, dopamine and water, and then performing a coating treatment, followed by drying and calcination to obtain the first catalyst.
[0043] In this application, the first catalyst, as the core catalytic component of the selective hydrogenation reaction, uses alumina as an inorganic support. After modification with citric acid, it forms a rich porous structure and active sites. Then, nickel phosphide is supported as the hydrogenation active center, and finally, a dense coating layer is formed with polydopamine. This process retains the high specific surface area and high mechanical strength of alumina, while the citric acid modification enhances the binding force between the active component and the support. The polydopamine coating layer, through hydrophobic interaction and adsorption properties, inhibits the deposition of gum and carbon deposits at the active sites, while also blocking the poisoning effect of alkaline nitrides on nickel phosphide. This improves the selective hydrogenation activity and long-term stability of the catalyst, enabling selective hydrogenation saturation of easily polymerizable olefins in gasoline without affecting isomeric olefins that contribute significantly to the octane number. Sulfides are converted into easily removable forms such as thiols and thioethers, laying the foundation for subsequent deep desulfurization.
[0044] In some embodiments, the alumina has an average particle size of 10-50 μm and a specific surface area of 150-300 m². 2 / g, with suitable pore volume and pore size distribution, can provide sufficient space for loading active sites.
[0045] In some embodiments, the mass-to-volume ratio of alumina, citric acid, and water is 1 g : (0.03~0.06) g : (1~3) mL. In some embodiments, the mass ratio of citric acid-modified alumina, nickel nitrate, and ammonium dihydrogen phosphate is 1 : (0.08~0.15) : (0.04~0.08).
[0046] In some embodiments, the mass-to-volume ratio of the alumina-supported nickel phosphide, dopamine, and water is 1 g : (0.02~0.05) g : (1~2) mL.
[0047] In some embodiments, the modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 40~60℃, and a time of 2~3 h. These conditions ensure that citric acid and alumina react fully to form a uniform modified layer.
[0048] In some embodiments, the reduction treatment is carried out under a hydrogen atmosphere at a temperature of 350-400°C for 3-4 hours, with a hydrogen flow rate of 50-100 mL / min, which can reduce nickel salts and phosphates to highly active nickel phosphide.
[0049] In some embodiments, the coating treatment is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 25~35℃, and a time of 2~3 h, which allows dopamine to be uniformly polymerized on the carrier surface to form a coating layer.
[0050] In some embodiments, the drying temperature is 90~110℃ and the time is 3~4h, which can remove residual moisture in the material and avoid affecting the roasting effect.
[0051] In some embodiments, the calcination is carried out under an inert atmosphere, with the inert gas being nitrogen or argon, at a flow rate of 50-100 mL / min, a temperature of 200-250°C, and a time of 2-3 h, which can further consolidate the bond between the polydopamine coating layer and the carrier.
[0052] In some embodiments, the preparation method of the second catalyst includes the following steps: mixing ZSM-5 molecular sieve, ethylenediaminetetraacetic acid (EDTA), and water, then modifying the mixture and drying it to obtain EDTA-modified ZSM-5 molecular sieve; mixing the EDTA-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate, then impregnating, calcining, and sulfiding the mixture to obtain ZSM-5 molecular sieve-supported cobalt molybdenum sulfide; and mixing the ZSM-5 molecular sieve-supported cobalt molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid, then coating and carbonizing the mixture to obtain the second catalyst.
[0053] In this application, the second catalyst, as the core catalytic component of the deep desulfurization reaction, uses ZSM-5 molecular sieve as an inorganic support. After modification with ethylenediaminetetraacetic acid (EDTA), the strength and distribution of acidic sites are regulated. Then, cobalt and molybdenum active components are loaded by impregnation and subjected to sulfidation treatment to form highly active cobalt-molybdenum sulfide. Finally, phenolic resin is used as a carbon source and p-toluenesulfonic acid is used as a catalyst. After coating and carbonization, a sulfonated carbon coating layer is formed. This process retains the excellent shape-selective catalytic performance and structural stability of ZSM-5 molecular sieve, while the EDTA modification optimizes the dispersibility of the active components. The cobalt-molybdenum sulfide provides the core active center for the deep hydrogenation removal of sulfides. The sulfonated carbon coating layer not only has a hydrophobic barrier effect but also assists in the adsorption and activation of sulfides through surface acidic sites, further improving the desulfurization efficiency. At the same time, it inhibits the damage of carbon deposits and corrosive media to the active components and extends the catalyst's service life.
[0054] In some embodiments, the ZSM-5 molecular sieve has a silica-to-alumina ratio of 20 to 50, an average particle size of 5 to 20 μm, and a specific surface area of 200 to 400 m². 2 / g, with suitable shape-selective channels and acidic sites.
[0055] In some embodiments, the mass-to-volume ratio of the ZSM-5 molecular sieve, ethylenediaminetetraacetic acid, and water is 1 g : (0.03~0.06) g : (1~3) mL.
[0056] In some embodiments, the mass ratio of the ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate is 1:(0.04~0.08):(0.10~0.20).
[0057] In some embodiments, the mass ratio of the ZSM-5 molecular sieve loaded with cobalt molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid is 1:(0.05~0.10):(0.02~0.05).
[0058] In some embodiments, the modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 50~70℃, and a time of 1.5~2.5 h, which can ensure that ethylenediaminetetraacetic acid and ZSM-5 molecular sieve react fully.
[0059] In some embodiments, the drying temperature is 90~110℃ and the time is 3~4h, which can remove residual moisture during the modification process.
[0060] In some embodiments, the impregnation process is an equal-volume impregnation, and the impregnation time is 8-12 hours, which can make cobalt and molybdenum ions uniformly dispersed in the carrier pores.
[0061] In some embodiments, the calcination temperature is 500~600℃ and the time is 3~4h, which can decompose the metal salt into metal oxide.
[0062] In some embodiments, the sulfidation treatment is carried out in a mixed atmosphere of hydrogen sulfide and hydrogen, with a hydrogen sulfide volume fraction of 5% to 10%, a temperature of 300 to 350°C, and a time of 4 to 6 hours, which can convert metal oxides into sulfide active phases.
[0063] In some embodiments, the coating treatment is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 60~80℃, and a time of 1~2 h, so that the phenolic resin can be uniformly coated on the surface of the carrier.
[0064] In some embodiments, the carbonization process is carried out under an inert atmosphere, with the inert gas being nitrogen or argon, at a temperature of 400-450°C for 3-4 hours, which can carbonize the phenolic resin to form a sulfonated carbon coating layer.
[0065] In some embodiments, the selective hydrogenation reaction is carried out under stirred conditions, with a stirring speed of 300-800 r / min, a temperature of 240-300 °C, a pressure of 1.6-2.5 MPa, a hydrogen-to-oil volume ratio of 200-400, and a liquid hourly space velocity of 2.0-4.0 h⁻¹. -1 .
[0066] The synergistic effect of the stirring speed and process parameters used in this application can ensure sufficient contact between the gas, liquid and solid phases and avoid uneven local reactions. The temperature and pressure parameters are matched with the activity window of nickel phosphide, which can not only ensure the conversion efficiency of sulfides, but also suppress the loss of octane number caused by excessive hydrogenation of olefins. The optimization of hydrogen-to-oil volume ratio and liquid hourly space velocity can balance reaction efficiency and catalyst utilization.
[0067] In some embodiments, the desulfurization reaction is carried out at a temperature of 300-330°C, a reaction pressure of 1.6-2.5 MPa, a hydrogen-to-oil volume ratio of 200-400, and a liquid hourly space velocity of 2.0-4.0 h⁻¹. -1 .
[0068] The process parameters are well-suited to the active characteristics of cobalt molybdenum sulfide. The higher reaction temperature promotes the deep hydrogenation removal of intermediate products such as thiols and thioethers, while the pressure and hydrogen-to-oil volume ratio provide a sufficient hydrogen atmosphere for the reaction, inhibiting catalyst carbon deposition and ensuring that the desulfurization rate remains stable at over 99%.
[0069] In some embodiments, the pretreatment of fluidized catalytic cracking gasoline specifically includes the following steps: mixing fluidized catalytic cracking gasoline, porous filter ceramic balls and dehydrating agent, purifying the mixture, and then separating the mixture to obtain pretreated fluidized catalytic cracking gasoline.
[0070] In some embodiments, the mass-to-volume ratio of the fluidized catalytic cracking gasoline, the porous filter ceramic ball, and the dehydrating agent is 1 g : (0.01~0.03) g : (0.02~0.05) mL.
[0071] In some embodiments, the purification process is carried out under stirring conditions, with a stirring speed of 300~500 r / min, a temperature of 25~35℃, and a time of 30~60 min.
[0072] In some embodiments, the porous filter ceramic balls are selected from alumina ceramic balls or silicon carbide ceramic balls with an average particle size of 1-5 mm, which have the characteristics of high strength and high wear resistance, and can remove mechanical impurities and gums in gasoline through physical adsorption. In some embodiments, the dehydrating agent is selected from one or more of 3A molecular sieve, 4A molecular sieve or 5A molecular sieve. It has a large adsorption capacity and excellent regeneration performance, and can effectively remove free water and dissolved water from gasoline, avoiding the damage of water to the active sites of the catalyst. The mechanical impurity content of the pretreated gasoline is ≤10μg / g and the moisture content is ≤50μg / g.
[0073] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0074] Example 1 This embodiment provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 850μg / g, octane number 92.5), 2g of alumina ceramic balls (average particle size 3mm), and 3mL of 4A molecular sieve dehydrating agent, and purifying the mixture at 30℃ and 400r / min for 45min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 300, and introducing the mixture into a fixed-bed reactor packed with a first catalyst, adjusting the temperature to 270℃, the pressure to 2.0MPa, and the liquid hourly space velocity to 3.0h. -1 The stirring speed was 500 r / min to carry out selective hydrogenation reaction. The reaction effluent was separated into gas and liquid phases to remove the gas phase containing hydrogen sulfide and collect the liquid phase product. The liquid-phase product was fed into a series of fixed-bed reactors packed with a second catalyst, and the temperature was adjusted to 310℃, the pressure to 2.0 MPa, the hydrogen-to-oil volume ratio to 300, and the liquid hourly space velocity to 3.0 h⁻¹. -1 The desulfurization reaction is carried out to obtain low-sulfur clean gasoline.
[0075] The preparation method of the first catalyst includes the following steps: 10g of alumina (average particle size 30μm, specific surface area 220m²) is added to... 2A mixture of 10g of citric acid, 0.4g of nickel nitrate, and 20mL of water was subjected to modification treatment at 50℃ and 500r / min for 2.5h to obtain citric acid-modified alumina. A mixture of 10g of citric acid-modified alumina, 1.2g of nickel nitrate, and 0.6g of ammonium dihydrogen phosphate was subjected to reduction treatment at 380℃ for 3.5h under a hydrogen atmosphere (flow rate 80mL / min) to obtain alumina-supported nickel phosphide. A mixture of 10g of alumina-supported nickel phosphide, 0.3g of dopamine, and 15mL of water was subjected to coating treatment at 30℃ and 700r / min for 2.5h, followed by drying at 100℃ for 3.5h, and then calcination at 220℃ for 2.5h under a nitrogen atmosphere (flow rate 80mL / min) to obtain the first catalyst.
[0076] The preparation method of the second catalyst includes the following steps: 10g of ZSM-5 molecular sieve (silicon-to-aluminum ratio 30, average particle size 15μm, specific surface area 300m²) is used. 2 0.4 g of ethylenediaminetetraacetic acid (EDTA) and 20 mL of water were mixed and modified at 60 °C and 500 r / min for 2 h, and then dried at 100 °C for 3.5 h to obtain EDTA-modified ZSM-5 molecular sieve; 10 g of EDTA-modified ZSM-5 molecular sieve, 0.6 g of cobalt nitrate and 1.5 g of ammonium molybdate were mixed and impregnated in equal volumes for 10 h, calcined at 550 °C for 3.5 h, and then sulfided at 320 °C for 5 h in a mixed atmosphere of hydrogen sulfide and hydrogen (hydrogen sulfide volume fraction 8%) to obtain ZSM-5 molecular sieve supported on cobalt molybdenum sulfide; 10g of ZSM-5 molecular sieve-supported cobalt molybdenum sulfide, 0.8g of phenolic resin and 0.3g of p-toluenesulfonic acid were mixed and coated at 70℃ and 700r / min for 1.5h, and then carbonized at 420℃ under nitrogen atmosphere for 3.5h to obtain the second catalyst.
[0077] Example 2 This embodiment provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 820μg / g, octane number 92.3), 1.5g of silicon carbide ceramic balls (average particle size 2mm), and 2mL of 3A molecular sieve dehydrating agent, and purifying the mixture at 28℃ and 350r / min for 40min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 250, and introducing the mixture into a fixed-bed reactor packed with a first catalyst, adjusting the temperature to 250℃, the pressure to 1.8MPa, and the liquid hourly space velocity to 2.5h. -1 The stirring speed was 400 r / min to carry out selective hydrogenation reaction. The reaction effluent was subjected to gas-liquid separation to remove the gas phase containing hydrogen sulfide and collect the liquid product. The liquid-phase product was fed into a series of fixed-bed reactors packed with a second catalyst, and the temperature was adjusted to 305℃, the pressure to 1.8MPa, the hydrogen-to-oil volume ratio to 250, and the liquid hourly space velocity to 2.5h⁻¹. -1 The desulfurization reaction is carried out to obtain low-sulfur clean gasoline.
[0078] The preparation method of the first catalyst includes the following steps: 10g of alumina (average particle size 20μm, specific surface area 250m²) is added to... 2 A mixture of 10g of citric acid, 0.3g of nickel nitrate, and 0.5g of ammonium dihydrogen phosphate was subjected to a reduction treatment at 360°C for 3 hours under a hydrogen atmosphere (flow rate 60mL / min) to obtain alumina-supported nickel phosphide. A mixture of 10g of alumina-supported nickel phosphide, 0.2g of dopamine, and 12mL of water was subjected to a coating treatment at 28°C and 650rpm for 2 hours, followed by drying at 95°C for 3 hours, and then calcination at 210°C for 2 hours under an argon atmosphere (flow rate 60mL / min) to obtain the first catalyst.
[0079] The preparation method of the second catalyst includes the following steps: 10g of ZSM-5 molecular sieve (silicon-to-aluminum ratio 25, average particle size 10μm, specific surface area 320m²) is used. 2 0.3 g of ethylenediaminetetraacetic acid (EDTA) and 15 mL of water were mixed and modified at 55 °C and 450 r / min for 1.8 h, then dried at 95 °C for 3 h to obtain EDTA-modified ZSM-5 molecular sieve. 10 g of EDTA-modified ZSM-5 molecular sieve, 0.5 g of cobalt nitrate, and 1.2 g of ammonium molybdate were mixed and impregnated in equal volumes for 9 h, calcined at 520 °C for 3 h, and then sulfided at 310 °C for 4.5 h in a mixed atmosphere of hydrogen sulfide and hydrogen (hydrogen sulfide volume fraction 6%) to obtain ZSM-5 molecular sieve-supported cobalt molybdenum sulfide. 10 g of ZSM-5 molecular sieve-supported cobalt molybdenum sulfide, 0.6 g of phenolic resin, and 0.2 g of p-toluenesulfonic acid were mixed and coated at 65 °C and 650 r / min for 1.2 h, then carbonized at 410 °C for 3 h in an argon atmosphere to obtain the second catalyst.
[0080] Example 3 This embodiment provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 880μg / g, octane number 92.7), 2.5g of alumina ceramic balls (average particle size 4mm), and 4mL of 5A molecular sieve dehydrating agent, and purifying the mixture at 32℃ and 450r / min for 50min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 350, and introducing the mixture into a fixed-bed reactor packed with a first catalyst, adjusting the temperature to 290℃, the pressure to 2.3MPa, and the liquid hourly space velocity to 3.5h. -1 The stirring speed was 600 r / min for selective hydrogenation. The reaction effluent was subjected to gas-liquid separation to remove the gas phase containing hydrogen sulfide and collect the liquid product. The liquid product was then passed into a series of fixed-bed reactors packed with a second catalyst, and the temperature was adjusted to 320℃, the pressure to 2.3 MPa, the hydrogen-to-oil volume ratio to 350, and the liquid hourly space velocity to 3.5 h⁻¹. -1 The desulfurization reaction is carried out to obtain low-sulfur clean gasoline.
[0081] The preparation method of the first catalyst includes the following steps: 10g of alumina (average particle size 40μm, specific surface area 180m²) is added to... 2 A mixture of 10g of citric acid, 0.6g of nickel nitrate, and 25mL of water was subjected to modification treatment at 55℃ and 550r / min for 3h to obtain citric acid-modified alumina. A mixture of 10g of citric acid-modified alumina, 1.4g of nickel nitrate, and 0.8g of ammonium dihydrogen phosphate was subjected to reduction treatment at 390℃ for 4h under a hydrogen atmosphere (flow rate 90mL / min) to obtain alumina-supported nickel phosphide. A mixture of 10g of alumina-supported nickel phosphide, 0.5g of dopamine, and 18mL of water was subjected to coating treatment at 32℃ and 750r / min for 3h, followed by drying at 105℃ for 4h, and then calcination at 240℃ under a nitrogen atmosphere (flow rate 90mL / min) for 3h to obtain the first catalyst.
[0082] The preparation method of the second catalyst includes the following steps: 10g of ZSM-5 molecular sieve (silicon-to-aluminum ratio 40, average particle size 18μm, specific surface area 280m²) is used. 20.6 g of ethylenediaminetetraacetic acid (EDTA) and 25 mL of water were mixed and modified at 65 °C and 550 r / min for 2.5 h, then dried at 105 °C for 4 h to obtain EDTA-modified ZSM-5 molecular sieve. 10 g of EDTA-modified ZSM-5 molecular sieve, 0.8 g of cobalt nitrate, and 1.8 g of ammonium molybdate were mixed and impregnated by equal volume for 11 h, calcined at 580 °C for 4 h, and then sulfided at 330 °C for 5.5 h in a mixed atmosphere of hydrogen sulfide and hydrogen (9% hydrogen sulfide by volume) to obtain ZSM-5 molecular sieve supported on cobalt molybdenum sulfide. 10 g of ZSM-5 molecular sieve supported on cobalt molybdenum sulfide, 1.0 g of phenolic resin, and 0.5 g of p-toluenesulfonic acid were mixed and coated at 75 °C and 750 r / min for 1.8 h, then carbonized at 440 °C in a nitrogen atmosphere for 4 h to obtain the second catalyst.
[0083] Comparative Example 1 This comparative example provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 850μg / g, octane number 92.5), 2g of alumina ceramic balls (average particle size 3mm), and 3mL of 4A molecular sieve dehydrating agent, and purifying the mixture at 30℃ and 400r / min for 45min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 300, and introducing the mixture into a fixed-bed reactor packed with a mixed catalyst, adjusting the temperature to 290℃, the pressure to 2.0MPa, and the liquid hourly space velocity to 3.0h. -1 The stirring speed is 500 r / min, and a one-stage hydrodesulfurization reaction is carried out to obtain gasoline.
[0084] The preparation method of the mixed catalyst includes the following steps: 10g of alumina and 10g of ZSM-5 molecular sieve are mixed as a composite support, and then mixed with 1.2g of nickel nitrate, 0.6g of ammonium dihydrogen phosphate, 0.6g of cobalt nitrate and 1.5g of ammonium molybdate. The mixture is impregnated with the same volume for 10h, calcined at 550℃ for 3.5h, and then sulfided at 320℃ for 5h in a mixed atmosphere of hydrogen sulfide and hydrogen (hydrogen sulfide volume fraction 8%) to obtain the mixed catalyst (without coating layer).
[0085] Comparative Example 2 This comparative example provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 850μg / g, octane number 92.5), 2g of alumina ceramic balls (average particle size 3mm), and 3mL of 4A molecular sieve dehydrating agent, and purifying the mixture at 30℃ and 400r / min for 45min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 300, and introducing the mixture into a fixed-bed reactor packed with a first catalyst, adjusting the temperature to 270℃, the pressure to 2.0MPa, and the liquid hourly space velocity to 3.0h. -1The stirring speed was 500 r / min for selective hydrogenation. The reaction effluent was subjected to gas-liquid separation to remove the gas phase containing hydrogen sulfide and collect the liquid product. The liquid product was then fed into a series of fixed-bed reactors packed with a second catalyst, and the temperature was adjusted to 310℃, the pressure to 2.0 MPa, the hydrogen-to-oil volume ratio to 300, and the liquid hourly space velocity to 3.0 h⁻¹. -1 The product gasoline is obtained by undergoing a desulfurization reaction.
[0086] The preparation method of the first catalyst includes the following steps: 10g of alumina, 0.4g of citric acid and 20mL of water are mixed and modified at 50℃ and 500r / min for 2.5h to obtain citric acid modified alumina; 10g of citric acid modified alumina, 1.2g of nickel nitrate and 0.6g of ammonium dihydrogen phosphate are mixed and reduced at 380℃ for 3.5h in a hydrogen atmosphere (flow rate 80mL / min) to obtain the first catalyst (without coating layer).
[0087] The preparation method of the second catalyst includes the following steps: 10g of ZSM-5 molecular sieve, 0.4g of ethylenediaminetetraacetic acid (EDTA) and 20mL of water are mixed and modified at 60℃ and 500r / min for 2h, and then dried at 100℃ for 3.5h to obtain EDTA-modified ZSM-5 molecular sieve; 10g of EDTA-modified ZSM-5 molecular sieve, 0.6g of cobalt nitrate and 1.5g of ammonium molybdate are mixed and impregnated in equal volumes for 10h, calcined at 550℃ for 3.5h, and then sulfided at 320℃ for 5h in a mixed atmosphere of hydrogen sulfide and hydrogen (hydrogen sulfide volume fraction 8%) to obtain the second catalyst (without coating layer).
[0088] Comparative Example 3 This comparative example provides a method for hydrodesulfurization of gasoline, comprising the following steps: mixing 100g of fluidized catalytic cracking gasoline (initial sulfur content 850μg / g, octane number 92.5), 2g of alumina ceramic balls (average particle size 3mm), and 3mL of 4A molecular sieve dehydrating agent, and purifying the mixture at 30℃ and 400r / min for 45min, obtaining pretreated gasoline after separation; mixing the pretreated gasoline with hydrogen at a hydrogen-to-oil volume ratio of 300, and introducing the mixture into a fixed-bed reactor packed with a first catalyst, adjusting the temperature to 270℃, the pressure to 2.0MPa, and the liquid hourly space velocity to 3.0h. -1 The stirring speed was 500 r / min for selective hydrogenation. The reaction effluent was subjected to gas-liquid separation to remove the gas phase containing hydrogen sulfide and collect the liquid product. The liquid product was then fed into a series of fixed-bed reactors packed with a second catalyst, and the temperature was adjusted to 310℃, the pressure to 2.0 MPa, the hydrogen-to-oil volume ratio to 300, and the liquid hourly space velocity to 3.0 h⁻¹. -1 The product gasoline is obtained by undergoing a desulfurization reaction.
[0089] The preparation method of the first catalyst includes the following steps: 10g of unmodified alumina, 1.2g of nickel nitrate and 0.6g of ammonium dihydrogen phosphate are mixed and reduced at 380℃ for 3.5h under a hydrogen atmosphere (flow rate 80mL / min) to obtain alumina-supported nickel phosphide; 10g of alumina-supported nickel phosphide, 0.3g of dopamine and 15mL of water are mixed and coated at 30℃ and 700r / min for 2.5h, then dried at 100℃ for 3.5h, and then calcined at 220℃ for 2.5h under a nitrogen atmosphere (flow rate 80mL / min) to obtain the first catalyst.
[0090] The preparation method of the second catalyst includes the following steps: 10g of unmodified ZSM-5 molecular sieve, 0.6g of cobalt nitrate and 1.5g of ammonium molybdate are mixed and impregnated by equal volume for 10h, calcined at 550℃ for 3.5h, and then sulfided at 320℃ for 5h in a mixed atmosphere of hydrogen sulfide and hydrogen (hydrogen sulfide volume fraction 8%) to obtain ZSM-5 molecular sieve supported cobalt molybdenum sulfide; 10g of ZSM-5 molecular sieve supported cobalt molybdenum sulfide, 0.8g of phenolic resin and 0.3g of p-toluenesulfonic acid are mixed and coated at 70℃ and 700r / min for 1.5h, and then carbonized at 420℃ in a nitrogen atmosphere for 3.5h to obtain the second catalyst.
[0091] The sulfur content and octane number loss of the gasoline products prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the stability of the catalyst (desulfurization rate retention rate after continuous operation for 3000 h) was also tested. The test results are shown in Table 1.
[0092] Table 1 Performance Test Results Item Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Sulfur content of product (μg / g) 6.2 5.8 7.1 45.3 18.7 22.5 Octane loss (unit) 1.1 1.0 1.3 3.8 1.8 2.1 Catalyst stability (3000h desulfurization rate retention, %) 95.8 96.5 94.2 68.3 75.6 78.9 As shown in Table 1, the low-sulfur clean gasoline prepared in Examples 1-3 of this application all had a sulfur content ≤7.1 μg / g and an octane number loss ≤1.3 units. After 3000 hours of continuous catalyst operation, the desulfurization retention rate remained ≥94.2%, demonstrating the core advantages of this method: ultra-deep desulfurization, low octane number loss, and long-term stable operation. Comparative Example 1, using a single catalyst without a core-shell structure and a one-stage reaction, lacked the stepwise synergy of selective hydrogenation and deep desulfurization, and had no coating layer to protect the catalyst's active sites, resulting in a significantly lower sulfur content in the product. The catalyst showed a significant increase in sulfur content and octane number loss of 3.8 units, resulting in a substantial decrease in catalyst stability, which could not meet environmental protection requirements and the needs of long-term industrial operation. The catalyst in Comparative Example 2 had no coating layer, and although it adopted a two-stage process, the active sites were susceptible to carbon deposition and poisoning. The product sulfur content and octane number loss were worse than those of the examples, and the catalyst stability was also significantly reduced. The catalyst in Comparative Example 3 did not undergo support modification, resulting in poor dispersion of active components, decreased catalytic efficiency, and the product sulfur content and octane number loss could not reach the levels of the examples. The catalyst stability was also affected.
[0093] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for hydrodesulfurization of gasoline, characterized in that, Includes the following steps: Fluidized catalytic cracking gasoline is pretreated and then mixed with hydrogen for selective hydrogenation, and the liquid phase product is collected. The liquid phase product is subjected to a desulfurization reaction to obtain low-sulfur clean gasoline; The selective hydrogenation reaction is carried out under the catalysis of a first catalyst, which has a core-shell structure. The core part of the first catalyst is citric acid-modified alumina supported on nickel phosphide, and the outer part of the first catalyst is polydopamine. The preparation method of the first catalyst includes the following steps: Alumina, citric acid and water are mixed and then modified to obtain citric acid-modified alumina. The citric acid-modified alumina, nickel nitrate, and ammonium dihydrogen phosphate were mixed and then reduced to obtain alumina-supported nickel phosphide. The alumina-supported nickel phosphide, dopamine, and water were mixed and coated, then dried and calcined to obtain the first catalyst. The coating process is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 25~35℃, and a time of 2~3 h; The drying temperature is 90~110℃, and the time is 3~4 hours; The calcination is carried out under an inert atmosphere at a temperature of 200-250°C for 2-3 hours. The desulfurization reaction is carried out under the catalysis of a second catalyst, which has a core-shell structure. The core part of the second catalyst is cobalt molybdenum sulfide supported on ZSM-5 molecular sieve modified with ethylenediaminetetraacetic acid, and the outer part of the second catalyst is a carbon sulfonate coating layer. The method for preparing the second catalyst includes the following steps: ZSM-5 molecular sieve, ethylenediaminetetraacetic acid (EDTA) and water were mixed, modified, and then dried to obtain EDTA-modified ZSM-5 molecular sieve. After mixing the ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate, the mixture was impregnated, calcined, and sulfided to obtain ZSM-5 molecular sieve loaded with cobalt molybdenum sulfide. The ZSM-5 molecular sieve was loaded with cobalt molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid, and then coated and carbonized to obtain a second catalyst.
2. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The mass-to-volume ratio of the alumina, citric acid, and water is 1 g : (0.03~0.06) g : (1~3) mL; and / or The mass ratio of citric acid-modified alumina, nickel nitrate, and ammonium dihydrogen phosphate is 1:(0.08~0.15):(0.04~0.08); and / or The mass-to-volume ratio of the alumina-supported nickel phosphide, dopamine, and water is 1 g : (0.02~0.05) g : (1~2) mL; and / or The modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 40~60℃, and a time of 2~3 h; and / or The reduction process is carried out in a hydrogen atmosphere at a temperature of 350-400°C for 3-4 hours.
3. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The mass-to-volume ratio of the ZSM-5 molecular sieve, ethylenediaminetetraacetic acid, and water is 1 g : (0.03~0.06) g : (1~3) mL; and / or The mass ratio of the ethylenediaminetetraacetic acid-modified ZSM-5 molecular sieve, cobalt nitrate, and ammonium molybdate is 1:(0.04~0.08):(0.10~0.20); and / or The ZSM-5 molecular sieve is loaded with cobalt molybdenum sulfide, phenolic resin, and p-toluenesulfonic acid in a mass ratio of 1:(0.05~0.10):(0.02~0.05); and / or The modification treatment is carried out under stirring conditions, with a stirring speed of 400~600 r / min, a temperature of 50~70℃, and a time of 1.5~2.5 h; and / or The drying temperature is 90~110℃, and the time is 3~4 hours; and / or The vulcanization treatment temperature is 280~320℃, and the time is 4~6h; and / or The coating treatment is carried out under stirring conditions, with a stirring speed of 600~800 r / min, a temperature of 60~80℃, and a time of 1~2 h; and / or The carbonization process is carried out under an inert atmosphere at a temperature of 400-450°C for 3-4 hours.
4. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The selective hydrogenation reaction is carried out under stirred conditions at a speed of 300–800 r / min, a temperature of 240–300 °C, a pressure of 1.6–2.5 MPa, a hydrogen-to-oil volume ratio of 200–400, and a liquid hourly space velocity of 2.0–4.0 h⁻¹. -1 .
5. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The desulfurization reaction is carried out at a temperature of 300-330℃, a reaction pressure of 1.6-2.5 MPa, a hydrogen-to-oil volume ratio of 200-400, and a liquid hourly space velocity of 2.0-4.0 h⁻¹. -1 .
6. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The pretreatment of fluidized catalytic cracked gasoline specifically includes the following steps: Fluidized catalytic cracking gasoline, porous filter ceramic balls, and dehydrating agent are mixed, purified, and then separated to obtain pretreated fluidized catalytic cracking gasoline.
7. The gasoline hydrodesulfurization method according to claim 6, characterized in that, The mass-to-volume ratio of the fluidized catalytic cracking gasoline, porous filter ceramic balls, and dehydrating agent is 1 g : (0.01~0.03) g : (0.02~0.05) mL; and / or The purification process is carried out under stirring conditions, with a stirring speed of 300~500 r / min, a temperature of 25~35℃, and a time of 30~60 min.
8. The gasoline hydrodesulfurization method according to claim 1, characterized in that, The low-sulfur clean gasoline has a sulfur content ≤10μg / g and an octane number loss ≤1.5 units.
Citation Information
Patent Citations
Preparation method and hydrogenation application of immobilized catalyst
CN103418413A
Catalytic cracking gasoline hydro-upgrading method
CN114075453A
